Early endarterectomy carries a lower procedural risk than early stenting in patients with symptomatic stenosis of the internal carotid artery: results from 4 randomized controlled trials - Rantner, Barbara; Ringleb, Peter A. (Stroke, 2017)
Background and Purpose: Patients undergoing carotid endarterectomy (CEA) for symptomatic stenosis of the internal carotid artery benefit from early intervention. Heterogeneous data are available on the influence of timing of carotid artery stenting (CAS) on procedural risk. Methods: We investigated the association between timing of treatment (0-7 days and >7 days after the qualifying neurological event) and the 30-day risk of stroke or death after CAS or CEA in a pooled analysis of individual patient data from 4 randomized trials by the Carotid Stenosis Trialists’ Collaboration. Analyses were done per protocol. To obtain combined estimates, logistic mixed models were applied. Results: Among a total of 4138 patients, a minority received their allocated treatment within 7 days after symptom onset (14% CAS versus 11% CEA). Among patients treated within 1 week of symptoms, those treated by CAS had a higher risk of stroke or death compared with those treated with CEA: 8.3% versus 1.3%, risk ratio, 6.7; 95% confidence interval, 2.1 to 21.9 (adjusted for age at treatment, sex, and type of qualifying event). For interventions after 1 week, CAS was also more hazardous than CEA: 7.1% versus 3.6%, adjusted risk ratio, 2.0; 95% confidence interval, 1.5 to 2.7 (P value for interaction with time interval 0.06). Conclusions: In randomized trials comparing stenting with CEA for symptomatic carotid artery stenosis, CAS was associated with a substantially higher periprocedural risk during the first 7 days after the onset of symptoms. Early surgery is safer than stenting for preventing future stroke.
Originally published: 28 Apr 2017
Gesehen am 31.07.2018